Interleukin-17 in various ocular surface inflammatory diseases - Kang, Min Ho; Kim, Mee Kum; Lee, Hyun Joo; Lee, Hyeon Il; Wee, Won Ryang; Lee, Jin Hak (Journal of Korean medical science, 2011)
Recently, the association of Th-17 cells or IL-17 with ocular inflammatory diseases such as uveitis, scleritis and dry eye syndrome was discovered. We assessed whether interleukin (IL)-17 was present in the tears of various ocular surface inflammatory diseases and the tear IL-17 concentrations were clinically correlated with various ocular surface inflammatory diseases. We measured concentrations of IL-17 in tears of normal subjects (n = 28) and patients (n = 141) with meibomian gland dysfunction (MGD), dry eye syndrome (DES), Sjögren syndrome (SS), Stevens-Johnson syndrome (SJS), graft-versus-host disease (GVHD), filamentary keratitis, and autoimmune keratitis associated with rheumatoid arthritis or systemic lupus erythematosus. Clinical epitheliopathy scores were based on the surface area of corneal and conjunctival fluorescein staining. The mean concentrations of IL-17 in tears of patients with filamentary keratitis, GVHD, autoimmune keratitis, SS, DES, MGD, SJS were significantly higher in order than that in normal subjects. Tear IL-17 concentration was significantly correlated with clinical epitheilopathy scores in the patients with systemic inflammatory disease, while tear IL-17 was not correlated with clinical severity of the cornea and conjunctiva in the dry eye patients without any systemic inflammatory disease. Tear IL-17 is likely to correlate clinically with corneal disease severity only in the patients with systemic inflammatory disease.